HUBUNGAN SANITASI LINGKUNGAN PERUMAHAN DAN PERILAKU MASYARAKAT DENGAN KEJADIAN FILARIASIS DI KECAMATAN KAMPUNG RAKYAT KABUPATEN LABUHAN BATU SELATAN TAHUN 2012 - Erwin Saleh Pulungan; Devi Nuraini Santi; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Relation between house environment sanitation and people’s behavior with the incidence of Filariasis in Kampung Rakyat subdistrict Labuhan Batu Selatan regency 2012.Filariasis is a chronic infectious disease which is caused by the infection of nematode parasite, lymphatic filaria transmitted by Mansonia, Anopheles and Culex mosquitos. Filariasis is also known as elephantiasis. The purpose of this research is to study the relation between house environment sanitation including waste drainage system, mosquitos breeding sites, mosquitos resting sites, ventilation with insect-proof gauze, room lighting, wall density, room moisture level, with the people’s behavior including knowledge, attitude and practice in Kampung Rakyat subdistrict Labuhan Batu Selatan regency 2012. This is an analytical survey with case control design. Population for this research is the people suffering from Filariasis which are 20 persons and the control is the people who don’t suffer from Filariasis which are 20 persons. Results from this research show that knowledge and practice have significant relation with the incidence of Filariasis. House environment sanitasion including waste drainage system (p=0,057), mosquitos breeding sites (p=0,157), ventilation with insect-proof gauze (p=0,177), wall density (p=0,122),room lighting (p=0,500), moisture level (p=0122,) all has no significant relation with the incidence of Filariasis analysed with chi-square test, the only one that has a significant relation is mosquitos resting site (p=0,026). The people are suggested to wear long-sleveed clothing and trousers as self-protection when going out at night time, use mosquito-net for sleeping, promote sanitation for house environment and do a community self-help. Key word : Filariasis, house enviroment sanitation, behavior